Size-fecundity relationships and reproductive investment in female frogs in the Pantanal, south-western Brazil - Prado, Cynthia P. A. [UNESP]; Haddad, Célio F. B. [UNESP] (My University, 2005)
The ovarian complement of anurans exhibiting different reproductive modes is highly diverse, and intraspecific variation in reproductive output of anurans is generally related to variation in female properties and/or environmental conditions. The size-fecundity relationships, reproductive investment, and correlation between ovary mass and fat body mass were investigated for females of an anuran assemblage in the Pantanal, Brazil. Female body size was positively correlated with clutch size among seven of the eight species analyzed. However, these results seem to be influenced by seasonal variation in fecundity. Interspecific size-fecundity relationships revealed that female SVL was positively correlated with clutch size and egg size regardless of reproductive mode. Among 11 species analyzed, the reproductive investment (RI: ovary mass relative to body mass) varied from 5.5 to 18%, and there were no differences among reproductive modes and activity patterns (explosive/prolonged). RI correlated negatively with female size. Among three Leptodactylus species examined, negative correlation between ovary mass and fat body mass was verified for two species. Variations in the reproductive strategies are closely related to the reproductive activity patterns and reproductive modes exhibited by individual species, but are also influenced by environmental conditions. However, regardless of reproductive mode or activity pattern, each species seems to exhibit a reproductive strategy that allows them to respond differently to the same environmental restrictions.
Keywords: Anurans; Clutch size; Fat body mass; Reproductive investment; Anura; Leptodactylus